ENHANCING STUDENTS' LITERACY: CANVA AND QUIZIZZ AS DIGITAL MULTIMODAL TOOLS - Tilana, Febriana Putri; Dewi, Dian Novita (English Review: Journal of English Education, 2024)
In this current era, the use of technology in daily activities is not something new for Indonesian people. Almost all activities in various fields already use technology, especially in education. In education, technology is very necessary as a reform effort that can stimulate students' abilities in the learning process to be more effective and efficient. The use of technology in learning can be used when preparing and even using learning media. The aim of this research is to describe the effect of using the Canva and Quizizz applications as digital multimodal texts in improving students' literacy skills. This research uses mixed methods. Data collection was obtained through 2 stages, namely a questionnaire to obtain quantitative data and interviews to obtain qualitative data for 10 grades students at Panjura High School Malang, total 89 students. Researchers used SPSS 26.0 and Microsoft Excel to process research data. The results of this research show that digital multimodal texts have positive influence on students' literacy skills in learning English. This is proven by the highest average score for each indicator, an average of 3.12 on the audio/video indicator; 3.22 on visual design; 3.16 on expression and voice; 3.18 on gestures and 2.99 on spatial position. In terms of implementation, students' motivation and enthusiasm for literacy in learning English increases due to the use of appropriate and innovative learning media.Keywords: Digital multimodal texts; students’ literacy skills; Canva; Quizizz